Firm leverage: Growth dynamics in low interest rate environment - Heponiemi, Ville (My University, 2024)
The selection of a capital structure stands as one of the pivotal decisions shaping a firm's finan-cial landscape. Although Modigliani and Miller (1958) assert the irrelevance of capital structure, real-world financial conditions often do not align with the assumptions underlying this state-ment. Various theories on capital structure have been proposed, yet a consensus on which theo-ry represents the norm remains elusive. This complexity impedes the examination of capital structure's impact on firm operations. A significant question arises regarding how leverage influ-ences a firm's investments and growth. This thesis aims to contribute to the ongoing discourse on the relationship between firm leverage and its impact on firm growth, measured through employment, capital expenditure growth, and net investments. It adopts a methodology similar to that originated in Lang et al. (1996). This study utilizes the US dataset from 2010 to 2018. To be included, firms must possess a Stand-ard Industrial Classification (SIC) code falling between 2000 and 3999 (to minimize regulatory effects) and maintain annual sales of at least $1 billion in any given year, measured in 2010 USD. The final dataset comprises 159 companies, yielding approximately 900 to 1,500 firm-year obser-vations, depending on the specific growth measure under examination: net investment, one-year and three-year employment growth rates, and one-year and three-year capital expenditure growth rates. In addition to book leverage, the independent variable, control variables such as sales growth, capital expenditures, cash flow, and Tobin's q are incorporated into the regression model. The results suggest that in positive business cycle periods like the 2010s, there is no correlation between leverage and firm growth. Over the sample period, the average leverage level of the companies in the dataset increased gradually from 28% to 35%. Concurrently, the US economy rebounded from the financial crisis and received support from government interventions. This had an impact on corporate earnings, employment, and capital expenditures.

Valitessaan pääomarakennetta yritys tekee yhden keskeisimmistä taloudellista asemaa muokkaavista päätöksistä. Vaikka Modigliani ja Miller (1958) väittävät, että pääomarakenteella ei ole merkitystä, todelliset taloudelliset olosuhteet eivät usein vastaa tämän väitteen taustalla olevia oletuksia. Erilaisia pääomarakenneteorioita on ehdotettu, mutta yhteisymmärrystä siitä, mikä teoria edustaa normia, ei ole saavutettu. Tämä ristiriitaisuus vaikeuttaa pääomarakenteen vaikutuksen tutkimista yrityksen toimintaan. Merkittävä kysymys on, kuinka velkaantuneisuus vaikuttaa yrityksen investointeihin ja kasvuun. Tämä tutkielma pyrkii edistämään keskustelua yrityksen velkaantuneisuuden ja sen kasvun vaikutusten suhteesta, mitattuna työllisyydellä, investointimenojen kasvulla ja nettoinvestoinneilla. Tutkimuksessa käytetään Lang et al. (1996) -tutkimuksesta lähtöisin olevaa menetelmää. Tutkielma hyödyntää Yhdysvaltain data-aineistoa vuosilta 2010-2018. Mukaan otettavien yritysten on oltava Standard Industrial Classification (SIC) -koodin 2000 ja 3999 välillä (regulatiivisten vaikutusten minimoimiseksi) ja niiden vuosittaisten liikevaihdon on oltava vähintään miljardi (US) dollaria minä tahansa vuonna, mitattuna vuoden 2010 Yhdysvaltain dollareina. Lopullinen aineisto käsittää 159 yritystä, mikä tarkoittaa noin 900–1500 yritysvuosi-havaintoa riippuen tarkasteltavasta kasvumittarista: nettosijoitukset, yhden ja kolmen vuoden työllisyyskasvu sekä yhden ja kolmen vuoden investointimenojen kasvu. Riippumattomana muuttujana olevan kirjanpidollisen velkaantuneisuuden lisäksi regressiomalliin sisällytetään kontrollimuuttujia, kuten myynnin kasvu, investointimenot, kassavirta ja Tobinin q. Tulokset viittaavat siihen, että positiivisina suhdannekausina, kuten 2010-luvulla, ei ole korrelaatiota velkaantuneisuuden ja yrityksen kasvun välillä. Aineistossa mukana olevien yritysten keskimääräinen velkaantumisaste kasvoi asteittain 28 prosentista 35 prosenttiin tarkastelujakson aikana. Samanaikaisesti Yhdysvaltain talous elpyi finanssikriisistä ja sai tukea hallituksen interventioista. Tämä vaikutti yritysten tuloksiin, työllisyyteen ja investointimenoihin positiivisesti.
Keywords: growth; finance; capital; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance